An experimental investigation of papaya oil methyl ester (POME) blends as potential alternate fuel for CI engine application. Issue 1 (31st December 2023) - Dinesh Kumar, V.; Hemadri, Vinayak B.; Chinnapandian, M.; Mrityunjayaswamy, K. M.
Abstract : When reliance on fossil fuels increased and costs escalated as a consequence of the precipitous decline in oil security and increased emissions, encourage green energy alternatives such as renewable fuels. The papaya seed, a second generation feedstock in this study, is used to produce papaya biodiesel by methanolysis. The properties of the test biodiesel and its mixtures are measured using a CI diesel engine at 1500 rpm. The load is applied to the engine in increments of 20% until it reaches its maximum level. The blend B25 is recommended as ideal as it resulted in better performance and emission characteristics, with the exception of nitrous oxide emissions. The ideal blend's specific fuel consumption, brake thermal efficiency, exhaust gas temperature, and smoke density are 0.27 kg/kW-hr, 30.93%, 318 0 C, and 49.02 HSU at maximum load. The emissions of carbon monoxide, hydrocarbon, and nitrous oxide were, 0.095 percent, 55, and 988 ppm. Highlights Performance emission and combustion of a compression ignition engine fueled with conventional fuel and papaya biodiesel and its blends were carried out. Engine parameters were determined for each blend of fuel at varying loads. Results revealed that the blend B25 is found optimum.